Bahasa Indonesia MENELAAH PERMASALAHAN YANG ADA DI SMK LEONARDO KLATEN BERKAITAN DENGAN KURIKULUM MERDEKA DAN PERAN GURU PPKn : Bahasa Indonesia - Ahmad Faizun; Dava Galuh Nurdiana; Fajar Rizki Maisaroh; Yogi Guntoro (LPPM Universitas Widya Dharma, 2024)
Abstract SMK Leonardo has been using the independent curriculum since 3 years ago, but there is one mechatronics department that still uses the 2016 KTSP curriculum. Teachers innovate by adjusting curriculum standards and student characteristics. Even though it has implemented an independent curriculum, SMK Leonardo still adapts its curriculum to the needs of students. Civics teachers play a role in shaping the character of students Teachers must be able to be role models and examples so that students can imitate them, in terms of discipline. Teach various values and norms, and help students understand each of these values and norms. Teachers become Motivators so that children can have good character. The teacher becomes a control. Teachers are expected to control every action taken by children, the way is by giving rewards and punishments. Cooperate with various parties to ensure the development of students towards a better direction. At SMK Lenonardo, the grading system uses a parameter system. To determine whether students have achieved the desired learning objectives. For summative assessment we do at the end of each chapter. In this assessment we set the KKM limit for PPKN lessons. If indeed students have not met the target value, they will be collected to be given additional lessons so that remidiation questions are given. Keywords: independent curriculum